Analisis Teks dan Kontekstual dalam Podcast Deddy Corbuzier bersama Aiman Witjaksono serta Relevansinya terhadap Materi Bahasa Indonesia di MA - Unaisatuz Zahro; Poppy Rachman; Magfirotul Hamdiah (Universitas Wijaya Kusuma Surabaya, 2026)
This study presents a textual and contextual analysis of the podcast featuring Deddy Corbuzier and Aiman Witjaksono using Teun A. Van Dijk’s critical discourse analysis model, and examines its relevance to the teaching of expository texts to 10th-grade students at MA Darut Tauhid in Krejengan, Probolinggo. This study employs a descriptive qualitative method, with data sources including podcast transcripts, observation results, interviews with teachers and students, and learning documentation. Data collection techniques involved observation, interviews, note-taking, and documentation, while data analysis was conducted through the stages of data condensation, data presentation, and drawing conclusions. The results of the study indicate that the macro structure of the podcast focuses on the development of artificial intelligence (AI) and its impact on human life. The podcast’s superstructure is systematically organized through an introduction, development of arguments, and conclusion. The micro structure is characterized by the use of persuasive, evaluative, and emotional language. In terms of social context and social cognition, the study explains the influence of social reality, knowledge, and the speaker’s experiences in constructing discourse. Additionally, the podcast is relevant as a medium for teaching expository texts because it can develop students’ critical thinking skills through information analysis and the construction of logical arguments.